Modified chemical fiber reinforced concrete and method for producing the same
Patent Information
- Application Number
- CN202410320964.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-20
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-03-20
AI Technical Summary
[0004]本发明的目的在于提供一种改性化学纤维增强混凝土及其制备方法,解决了化学纤维与混凝土基体之间的界面粘结强度偏低的问题,在较小的改性化学纤维掺量下,即可使改性化学纤维增强混凝土抗裂性能好,且强度高,同时混凝土生产成本低
[0025] In preparing fiber-reinforced concrete, this invention modifies the chemical fibers by coating them with hydrotalcite. The hydrotalcite coating on the surface of the chemical fibers reacts with cement to form calcium magnesium silicate gel, which improves the interfacial bond strength between the chemical fibers and the concrete matrix, enabling a firm connection between the chemical fibers and the concrete matrix. Furthermore, the reaction between hydrotalcite and cement effectively fills microcracks and pores in the concrete, reducing the voids between the chemical fibers and the concrete matrix. Therefore, coating the chemical fibers with hydrotalcite effectively leverages their bridging function, inhibits plastic shrinkage in concrete, thereby improving the crack resistance of the concrete and reinforcing it. Additionally, coating the chemical fibers with hydrotalcite also enhances their dispersibility.
Smart Images

Figure BDA0004750523850000081 
Figure BDA0004750523850000091 
Figure BDA0004750523850000092
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete technology, specifically to a modified chemical fiber reinforced concrete and its preparation method. Background Technology
[0002] Concrete typically exhibits brittle failure, while fibers can improve the ductility after cracking and enhance the mechanical properties of concrete. Fiber-reinforced concrete is a rapidly developing new type of composite material in recent years, with polypropylene fiber-reinforced concrete showing the fastest growth. It is widely used in highways, airports, bridges, hydraulic engineering, and construction due to its excellent impermeability, freeze-thaw resistance, abrasion resistance, and impact resistance.
[0003] Early-stage crack resistance of precast concrete components is a crucial performance indicator for prefabricated buildings. Based on current research and practical applications both domestically and internationally, using low-dosage chemical fiber concrete can address this issue. However, due to the thousands of chemical fibers per kilogram, the interfacial bond strength between the chemical fibers and the concrete matrix is relatively low, and voids are easily generated, thus affecting the workability of the concrete. Therefore, further research and development are needed to overcome the adverse effects of chemical fibers and maintain low production costs while improving the cost-effectiveness of components. Summary of the Invention
[0004] The purpose of this invention is to provide a modified chemical fiber reinforced concrete and its preparation method, which solves the problem of low interfacial bond strength between chemical fibers and concrete matrix. With a small amount of modified chemical fiber, the modified chemical fiber reinforced concrete can have good crack resistance and high strength, while the concrete production cost is low.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A modified chemical fiber reinforced concrete comprises the following raw materials: concrete matrix and modified chemical fibers; wherein the modified chemical fibers are hydrotalcite-coated chemical fibers.
[0007] Preferably, the amount of modified chemical fiber added is 0.8-1.5% of the mass of the concrete matrix.
[0008] Preferably, the preparation method of the hydrotalcite-coated chemical fiber includes the following steps: adding water and chemical fiber to a reaction vessel, stirring and dispersing, and heating to 50-55°C, then simultaneously adding a mixed salt solution and an alkaline solution dropwise to the reaction vessel while stirring. During the dropwise addition, the pH is controlled between 9 and 9.5. After the dropwise addition is completed, the reaction vessel is sealed, the temperature is raised to 80-85°C, and stirring is continued for 9-11 hours. Then, centrifugation, washing with water, and drying are performed to obtain the hydrotalcite-coated chemical fiber.
[0009] The mixed salt solution contains Mg 2+ Al 3+ A mixed salt solution, wherein the Mg 2+ Al 3+ The molar ratio is 2.5-3.1:1.
[0010] Preferably, the Al 3+ The molar concentration in the mixed salt solution is 0.1-0.3 mol / L;
[0011] The alkaline solution contains sodium hydroxide and sodium carbonate, with a molar concentration of sodium hydroxide of 0.2-0.3 mol / L and a molar concentration of sodium carbonate of 0.1-0.2 mol / L.
[0012] The mass-to-volume ratio of the chemical fiber to water and mixed salt solution is 1kg:90-130L:300-550L;
[0013] The dripping time is 50-80 minutes; the stirring speed is 200-300 r / min.
[0014] Preferably, when the mixed salt solution and alkali solution are added dropwise to the reaction vessel while stirring, ultrasonic treatment is also performed, with an ultrasonic power of 300-500W.
[0015] Preferably, the mixed salt solution also contains Zn. 2+ Ca 2+ Fe 3+ The Zn 2+ Ca 2+ Fe 3+ With Al 3+ The molar ratio is 1-1.3:0.5-0.8:0.5-0.7:1.
[0016] Preferably, the chemical fiber is polypropylene fiber, polyethylene fiber, or polyvinyl alcohol fiber; the diameter of the chemical fiber is 15-25 μm and the length is 8-13 mm.
[0017] Preferably, the modified chemical fiber reinforced concrete further includes the following raw materials: silica fume, limestone powder, and alum powder;
[0018] The mass ratio of silica fume, limestone powder, and alunite powder is 10:3-7:0.2-0.8;
[0019] The particle size of the silica fume, limestone powder, and alunite powder is ≤300 mesh.
[0020] The total amount of silica fume, limestone powder, and alum powder added is 1.2-1.7% of the mass of the concrete base material.
[0021] Preferably, the concrete base material is made by mixing cement, fly ash, coarse aggregate, fine aggregate, water-reducing agent, and water in a mass ratio of 100:25-40:200-240:180-210:0.5-0.9:45-54;
[0022] The cement is ordinary Portland cement; the fly ash is Grade II fly ash; the coarse aggregate is 5-10mm continuously graded crushed stone; the fine aggregate is river sand; and the water-reducing agent is polycarboxylate water-reducing agent.
[0023] As a general inventive concept, the present invention provides a method for preparing modified chemical fiber reinforced concrete, comprising the following steps: mixing cement, fly ash, coarse aggregate, and fine aggregate evenly, then adding water and water-reducing agent and stirring evenly to obtain concrete base material; then adding other raw materials containing modified chemical fibers to the concrete base material and stirring evenly to obtain the modified chemical fiber reinforced concrete.
[0024] The beneficial effects of this invention are:
[0025] In preparing fiber-reinforced concrete, this invention modifies the chemical fibers by coating them with hydrotalcite. The hydrotalcite coating on the surface of the chemical fibers reacts with cement to form calcium magnesium silicate gel, which improves the interfacial bond strength between the chemical fibers and the concrete matrix, enabling a firm connection between the chemical fibers and the concrete matrix. Furthermore, the reaction between hydrotalcite and cement effectively fills microcracks and pores in the concrete, reducing the voids between the chemical fibers and the concrete matrix. Therefore, coating the chemical fibers with hydrotalcite effectively leverages their bridging function, inhibits plastic shrinkage in concrete, thereby improving the crack resistance of the concrete and reinforcing it. Additionally, coating the chemical fibers with hydrotalcite also enhances their dispersibility.
[0026] This invention employs a double-drop method to prepare hydrotalcite-coated chemical fibers, controlling appropriate parameters such as temperature, time, pH value, and molar ratio of various metal elements at each stage to achieve better hydrotalcite coating on the chemical fiber surface. Furthermore, during the preparation of the hydrotalcite-coated chemical fibers, ultrasonic treatment is performed during the addition of mixed salt and alkali solutions, which improves the surface roughness of the prepared hydrotalcite-coated chemical fibers, enhances the adhesion to the concrete matrix, and results in fiber-reinforced concrete with higher crack resistance and strength.
[0027] This invention has found through research that the zinc-calcium-iron-aluminum-magnesium hydrotalcite-coated chemical fibers prepared can more effectively improve the crack resistance and strength of concrete compared to aluminum-magnesium hydrotalcite-coated chemical fibers.
[0028] The fiber-reinforced concrete of this invention, in addition to the addition of hydrotalcite-coated chemical fibers, also incorporates silica fume, limestone powder, and alum stone powder in appropriate mass ratios. This increases the generation of gelling substances, strengthens the bond between the fibers and the concrete, and further fills the micro-voids in the concrete matrix and between the fibers and the concrete matrix, making the overall concrete structure more stable and giving the fiber-reinforced concrete better strength and crack resistance.
[0029] This invention solves the problem of low interfacial bond strength between chemical fibers and concrete matrix. With a small amount of modified chemical fiber, the modified chemical fiber reinforced concrete can have good crack resistance and high strength, while the concrete production cost is low. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] In the following embodiments of the present invention, the cement used is 42.5 grade ordinary Portland cement, the fly ash is grade II fly ash, the coarse aggregate is 5-10mm continuously graded crushed stone, the fine aggregate is river sand, and the water-reducing agent is polycarboxylate water-reducing agent.
[0032] Example 1:
[0033] A modified chemical fiber reinforced concrete comprises the following raw materials: 100 parts concrete base material and 1 part modified chemical fiber.
[0034] The concrete base material is made by mixing cement, fly ash, coarse aggregate, fine aggregate, water-reducing agent, and water in a mass ratio of 100:35:240:200:0.5:50.
[0035] The modified chemical fiber is a hydrotalcite-coated chemical fiber. The preparation method of the hydrotalcite-coated chemical fiber includes the following steps: adding 100L of water and 1kg of chemical fiber to a reaction vessel, stirring and dispersing, and heating to 55℃. Then, while stirring (at a speed of 300r / min), Mg is added dropwise to the reaction vessel. 2+ Al 3+ The mixed salt solution and alkali solution were added dropwise, and the pH was controlled between 9 and 9.5. The total amount of mixed salt solution added was 550L. After the dropwise addition (dropwise time was 80min), the reaction vessel was sealed, the temperature was raised to 82℃ and stirring was continued for 11h. Then, centrifugation, washing with water and drying were performed to obtain hydrotalcite-coated chemical fibers.
[0036] The aforementioned chemical fiber is a polypropylene fiber with a diameter of 25 μm and a length of 10 mm.
[0037] The mixed salt solution is prepared by adding magnesium nitrate and aluminum nitrate to water, stirring until dissolved, and then obtaining the mixed salt solution. In the mixed salt solution, Al... 3+ The molar concentration is 0.2 mol / L, Mg 2+ The molar concentration is 0.56 mol / L.
[0038] The alkaline solution is prepared by adding sodium hydroxide and sodium carbonate to water, stirring until dissolved, and then obtaining the alkaline solution. The molar concentration of sodium hydroxide in the alkaline solution is 0.2 mol / L, and the molar concentration of sodium carbonate is 0.2 mol / L.
[0039] The above-mentioned method for preparing modified chemical fiber reinforced concrete includes the following steps: mixing cement, fly ash, coarse aggregate, and fine aggregate evenly, then adding water and water-reducing agent and stirring evenly to obtain concrete base material; then adding modified chemical fibers to the concrete base material and stirring evenly to obtain modified chemical fiber reinforced concrete.
[0040] Example 2:
[0041] A modified chemical fiber reinforced concrete comprises the following raw materials: 100 parts concrete base material and 0.8 parts modified chemical fiber.
[0042] The concrete base material is made by mixing cement, fly ash, coarse aggregate, fine aggregate, water-reducing agent, and water in a mass ratio of 100:25:200:210:0.9:45.
[0043] The modified chemical fiber is a hydrotalcite-coated chemical fiber. The preparation method of the hydrotalcite-coated chemical fiber includes the following steps: adding 90L of water and 1kg of chemical fiber to a reaction vessel, stirring and dispersing, and heating to 50℃. Then, while stirring (at a speed of 200r / min), Mg is added dropwise to the reaction vessel. 2+ Al 3+ The mixed salt solution and alkali solution were added dropwise, and the pH was controlled between 9 and 9.5. The total amount of mixed salt solution added was 300L. After the dropwise addition (dropwise time was 50min), the reaction vessel was sealed, the temperature was raised to 80℃ and stirring was continued for 10h. Then, centrifugation, washing with water and drying were performed to obtain hydrotalcite-coated chemical fibers.
[0044] The aforementioned chemical fiber is a polypropylene fiber with a diameter of 15μm and a length of 8mm.
[0045] The mixed salt solution is prepared by adding magnesium nitrate and aluminum nitrate to water, stirring until dissolved, and then obtaining the mixed salt solution. In the mixed salt solution, Al... 3+The molar concentration is 0.1 mol / L, Mg 2+ The molar concentration is 0.31 mol / L.
[0046] The alkaline solution is prepared by adding sodium hydroxide and sodium carbonate to water, stirring until dissolved, and then obtaining the alkaline solution. The molar concentration of sodium hydroxide in the alkaline solution is 0.3 mol / L, and the molar concentration of sodium carbonate is 0.2 mol / L.
[0047] The preparation method of the modified chemical fiber reinforced concrete is the same as in Example 1.
[0048] Example 3:
[0049] A modified chemical fiber reinforced concrete comprises the following raw materials: 100 parts concrete base material and 1.5 parts modified chemical fiber.
[0050] The concrete base material is made by mixing cement, fly ash, coarse aggregate, fine aggregate, water-reducing agent, and water in a mass ratio of 100:40:220:200:0.7:54.
[0051] The modified chemical fiber is a hydrotalcite-coated chemical fiber. The preparation method of the hydrotalcite-coated chemical fiber includes the following steps: adding 130L of water and 1kg of chemical fiber to a reaction vessel, stirring and dispersing, and heating to 52℃. Then, while stirring (at a speed of 260r / min), Mg is added dropwise to the reaction vessel. 2+ Al 3+ The mixed salt solution and alkali solution were added dropwise, and the pH was controlled between 9 and 9.5. The total amount of mixed salt solution added was 450L. After the dropwise addition (dropwise time was 80min), the reaction vessel was sealed, the temperature was raised to 85℃ and stirring was continued for 9h. Then, centrifugation, washing with water and drying were performed to obtain hydrotalcite-coated chemical fibers.
[0052] The aforementioned chemical fiber is a polypropylene fiber with a diameter of 22 μm and a length of 13 mm.
[0053] The mixed salt solution is prepared by adding magnesium nitrate and aluminum nitrate to water, stirring until dissolved, and then obtaining the mixed salt solution. In the mixed salt solution, Al... 3+ The molar concentration of Mg is 0.3 mol / L. 2+ The molar concentration is 0.75 mol / L.
[0054] The alkaline solution is prepared by adding sodium hydroxide and sodium carbonate to water, stirring until dissolved, and then obtaining the alkaline solution. The molar concentration of sodium hydroxide in the alkaline solution is 0.2 mol / L, and the molar concentration of sodium carbonate is 0.1 mol / L.
[0055] The preparation method of the modified chemical fiber reinforced concrete is the same as in Example 1.
[0056] Example 4:
[0057] A modified chemical fiber reinforced concrete differs from Example 1 in that the mixed salt solution is prepared by adding magnesium nitrate, aluminum nitrate, zinc nitrate, calcium nitrate, and ferric nitrate to water, stirring to dissolve them, and then obtaining the mixed salt solution. In the mixed salt solution, Al... 3+ The molar concentration is 0.2 mol / L, Mg 2+ The molar concentration of Zn is 0.56 mol / L. 2+ The molar concentration is 0.2 mol / L, Ca 2+ The molar concentration was 0.16 mol / L, Fe 3+ The molar concentration is 0.1 mol / L.
[0058] Example 5:
[0059] A modified chemical fiber reinforced concrete differs from Example 1 in that the mixed salt solution is prepared by adding magnesium nitrate, aluminum nitrate, zinc nitrate, calcium nitrate, and ferric nitrate to water, stirring to dissolve them, and then obtaining the mixed salt solution. In the mixed salt solution, Al... 3+ The molar concentration is 0.2 mol / L, Mg 2+ The molar concentration of Zn is 0.56 mol / L. 2+ The molar concentration is 0.26 mol / L, Ca 2+ The molar concentration is 0.1 mol / L, Fe 3+ The molar concentration is 0.14 mol / L.
[0060] Example 6:
[0061] A modified chemical fiber reinforced concrete differs from Example 1 in that, in the method for preparing hydrotalcite-coated chemical fibers, ultrasonic treatment is also performed while simultaneously adding a mixed salt solution and an alkali solution to the reaction vessel with stirring. The ultrasonic power is 500W.
[0062] Example 7:
[0063] A modified chemical fiber reinforced concrete differs from Example 4 in that, in the method for preparing hydrotalcite-coated chemical fibers, ultrasonic treatment is also performed while simultaneously adding a mixed salt solution and an alkali solution to the reaction vessel with stirring. The ultrasonic power is 300W.
[0064] Example 8:
[0065] A modified chemical fiber reinforced concrete, which differs from Example 1, further includes the following raw materials: silica fume, limestone powder, and alum stone powder; the mass ratio of silica fume, limestone powder, and alum stone powder is 10:5:0.8; and the total amount of silica fume, limestone powder, and alum stone powder added is 1.5 parts.
[0066] The particle size of silica fume, limestone powder, and alum stone powder is ≤300 mesh.
[0067] The above-mentioned method for preparing modified chemical fiber reinforced concrete includes the following steps: mixing cement, fly ash, coarse aggregate, and fine aggregate evenly, then adding water and water-reducing agent and stirring evenly to obtain concrete base material; then adding silica fume, limestone powder, alum stone powder, and modified chemical fibers to the concrete base material and stirring evenly to obtain modified chemical fiber reinforced concrete.
[0068] Example 9:
[0069] A modified chemical fiber reinforced concrete, which differs from Example 4, further includes the following raw materials: silica fume, limestone powder, and alum stone powder; the mass ratio of silica fume, limestone powder, and alum stone powder is 10:3:0.2; and the total amount of silica fume, limestone powder, and alum stone powder added is 1.2 parts.
[0070] The particle size of silica fume, limestone powder, and alum stone powder is ≤300 mesh.
[0071] The preparation method of modified chemical fiber reinforced concrete is the same as in Example 8.
[0072] Example 10:
[0073] A modified chemical fiber reinforced concrete, which differs from Example 7 in that it further includes the following raw materials: silica fume, limestone powder, and alum stone powder; the mass ratio of silica fume, limestone powder, and alum stone powder is 10:6:0.6; and the total amount of silica fume, limestone powder, and alum stone powder added is 1.7 parts.
[0074] The particle size of silica fume, limestone powder, and alum stone powder is ≤300 mesh.
[0075] The preparation method of modified chemical fiber reinforced concrete is the same as in Example 8.
[0076] Comparative Example 1:
[0077] Unlike Example 1, the modified chemical fibers were replaced with unmodified chemical fibers. The unmodified chemical fibers were polypropylene fibers with a diameter of 25 μm and a length of 10 mm.
[0078] Comparative Example 2:
[0079] Unlike Example 1, the modified chemical fibers were replaced with a mixture of unmodified chemical fibers and magnesium-aluminum hydrotalcite at a mass ratio of 1:0.3. The unmodified chemical fibers were polypropylene fibers with a diameter of 25 μm and a length of 10 mm, and the magnesium-aluminum hydrotalcite had a magnesium to aluminum molar ratio of 2.8:1.
[0080] Performance testing:
[0081] 1. The crack resistance of concrete was tested using the early cracking sensitivity test method (plate method) for cement concrete. A flat thin plate specimen with dimensions of 600mm×600mm×63mm was used. The average cracking area and the number of cracks per unit area of each crack were tested. The test results are shown in Table 1.
[0082] Table 1. Test results for crack resistance of concrete
[0083]
[0084]
[0085] A comparison of Example 1 and Comparative Examples 1-2 shows that reinforcing concrete with hydrotalcite-coated chemical fibers significantly improves crack resistance compared to unmodified chemical fibers and unmodified chemical fiber / hydrotalcite mixtures. Furthermore, Examples 4-5, compared to Example 1, demonstrate that zinc-calcium-iron-aluminum-magnesium hydrotalcite-coated chemical fibers more significantly improves crack resistance than aluminum-magnesium hydrotalcite-coated chemical fibers. Comparisons of Examples 6 and 7 with Examples 1 and 4 respectively show that ultrasonic treatment during the preparation of hydrotalcite-coated chemical fibers results in fiber-reinforced concrete with higher crack resistance. Comparisons of Examples 7, 8, and 9 with Examples 1, 4, and 7 respectively show that, in addition to hydrotalcite-coated chemical fibers, the addition of appropriate mass ratios of silica fume, limestone powder, and alunite powder to the fiber-reinforced concrete also significantly improves crack resistance.
[0086] 2. In accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", concrete was prepared into test blocks of 0.1m×0.1m×0.1m, cured for 28 days, and the compressive strength and flexural strength corresponding to 28 days were tested. The specific test results are shown in Table 2.
[0087] Table 2 Concrete Strength Performance Test
[0088]
[0089]
[0090] As can be seen from the comparison of Example 1 and Comparative Examples 1-2, the reinforcement performance of concrete using hydrotalcite-coated chemical fibers is significantly improved compared to unmodified chemical fibers and unmodified chemical fiber / hydrotalcite mixtures. Furthermore, comparisons with data from other examples show that replacing aluminum-magnesium hydrotalcite-coated chemical fibers with zinc-calcium-iron-aluminum-magnesium hydrotalcite-coated chemical fibers, ultrasonic treatment during the preparation of hydrotalcite-coated chemical fibers, and adding appropriate mass ratios of silica fume, limestone powder, and alum stone powder to the concrete can all improve the strength of fiber-reinforced concrete to a certain extent.
[0091] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified chemical fiber reinforced concrete, characterized in that, The raw materials include: concrete base material and modified chemical fibers; the modified chemical fibers are hydrotalcite-coated chemical fibers. The concrete base material is made by mixing cement, fly ash, coarse aggregate, fine aggregate, water-reducing agent, and water in a mass ratio of 100:25-40:200-240:180-210:0.5-0.9:45-54. The modified chemical fiber is added at a rate of 0.8-1.5% of the concrete matrix mass. The preparation method of the hydrotalcite-coated chemical fiber includes the following steps: adding water and chemical fiber to a reaction vessel, stirring and dispersing, and heating to 50-55℃, then simultaneously adding a mixed salt solution and an alkaline solution dropwise to the reaction vessel while stirring. During the dropwise addition, the pH is controlled between 9 and 9.
5. After the dropwise addition is completed, the reaction vessel is sealed, the temperature is raised to 80-85℃ and stirring is continued for 9-11 hours, followed by centrifugation, washing with water, and drying to obtain the hydrotalcite-coated chemical fiber. The chemical fiber is polypropylene fiber, polyethylene fiber, or polyvinyl alcohol fiber; the mixed salt solution contains Mg. 2 + Al 3+ A mixed salt solution, wherein the Mg 2+ Al 3+ The molar ratio is 2.5-3.1:1; the mixed salt solution also contains Zn. 2+ Ca 2+ Fe 3+ The Zn 2+ Ca 2+ Fe 3+ With Al 3+ The molar ratio is 1-1.3:0.5-0.8:0.5-0.7:
1.
2. The modified chemical fiber reinforced concrete according to claim 1, characterized in that, The Al 3+ The molar concentration in the mixed salt solution is 0.1-0.3 mol / L; The alkaline solution contains sodium hydroxide and sodium carbonate, with a molar concentration of sodium hydroxide of 0.2-0.3 mol / L and a molar concentration of sodium carbonate of 0.1-0.2 mol / L. The mass-to-volume ratio of the chemical fiber to water and mixed salt solution is 1kg:90-130L:300-550L; The dripping time is 50-80 minutes; the stirring speed is 200-300 r / min.
3. The modified chemical fiber reinforced concrete according to claim 1, characterized in that, While stirring, the mixed salt solution and alkali solution are simultaneously added dropwise to the reaction vessel, and ultrasonic treatment is also performed with an ultrasonic power of 300-500W.
4. The modified chemical fiber reinforced concrete according to any one of claims 1-3, characterized in that, The chemical fibers have a diameter of 15-25 μm and a length of 8-13 mm.
5. The modified chemical fiber reinforced concrete according to any one of claims 1-3, characterized in that, The modified chemical fiber reinforced concrete also includes the following raw materials: silica fume, limestone powder, and alum stone powder; The mass ratio of silica fume, limestone powder, and alunite powder is 10:3-7:0.2-0.8; The particle size of the silica fume, limestone powder, and alunite powder is ≤300 mesh. The total amount of silica fume, limestone powder, and alum powder added is 1.2-1.7% of the mass of the concrete base material; The cement is ordinary Portland cement; the fly ash is Grade II fly ash; the coarse aggregate is 5-10mm continuously graded crushed stone; the fine aggregate is river sand; and the water-reducing agent is polycarboxylate water-reducing agent.
6. A method for preparing modified chemical fiber reinforced concrete as described in claim 1, characterized in that, The process includes the following steps: mixing cement, fly ash, coarse aggregate, and fine aggregate evenly, then adding water and water-reducing agent and stirring evenly to obtain concrete base material; then adding other raw materials containing modified chemical fibers to the concrete base material and stirring evenly to obtain the modified chemical fiber reinforced concrete.
Citation Information
Patent Citations
Preparation method of modified fibers having high interface binding strength with cement-based material
CN106977126A
Composite body of hydrotalcite and fiber
CN109562953A